Economic traits of indigenous goats of Bundelkhand region of Uttar Pradesh, under range management - Prasad, Rajendra; Singh, A K; Chaudhary, R P (Annals of Agricultural Research, 2016)
A Study was carried out to characterize the various economic traits of purely indigenous (Local)Â goats belonging to 70 flocks in seven district of Bundelkhand region of Uttar Pradesh. The goatsÂ are of medium size (72.30Â±2.52, 69.20Â±2.90 and 70.90Â±3.15 cm average body length, height andÂ heart girth in males, respectively), well built, reared mostly for meat production and have wellÂ adoption to agro climatic zones of Bundelkhand region. The coat colour varies from completeÂ grayish, admixture of white and brown, black and brown or complete black also. The goats are ofÂ migratory nature. Flock size varies from 20 to 85 with an average of 45. Goats are housed duringÂ nights in temporarily thatched shed supported by wooden or bamboo sticks with an earthen floor.Â The goats are maintained solely on grazing without supplementary feeding, except during kiddingÂ or sickness. They are allowed for grazing daily 6-7 hours throughout the year. Inbreeding isÂ followed, since long back from the males, available in their existing own flock. The average bodyÂ weights of male at birth, 3, 6, 9, 12 and 18 months of ages were 2.10Â±0.09, 8.42Â±0.35, 13.90Â±1.01,Â 17.02Â±1.60, 23.05Â±1.90 and 27.50Â±2.50 kg respectively. Corresponding body weights of femalesÂ were 1.84Â±0.07, 7.80Â±0.42, 12.90Â±0.69, 17.02Â±1.60, 19.30Â±1.12 and 24.53Â±1.20 kg respectively. TheÂ average age at first kidding and kidding interval were 598Â±2.92 and 295.80Â±2.87 days respectively.Â The twins and triplets recorded were 51.4 and 5.75% respectively. The average milk yield recordedÂ was 0.55Â±0.17 litre a day. The lactation yield was 91.50Â±1.15 litre in 142Â±0.97 days. The overallÂ average mortality was 6.75% in pre-weaned kids and 4.9% in adults, in lack of suitable controlÂ measure. The net return/goat was Rs. 1,002 with a BC ratio of 1.57. The most populous, indigenousÂ goats have enormous capacity to contribute well with minimum inputs to the livelihood of resourceÂ poor’s, due to its overall performances and the improvements in their existing feeding, breeding,Â housing and health management practices will prove a very effective tool for rural employmentÂ and income generation in the region.